Performance of Pseudaletia sequax (Lep.: Noctuidae) in natural and artificial diels - Salvadori, José Roberto; Parra, José Roberto Postali (Pesquisa Agropecuaria Brasileira, 2014)
Pseudaletia sequax Franc., 1951 (Lep.: Noctuidae) was studied on wheat leaves and on three artificial dieta, in laboratory under controlled conditions (temperature: 25 ± 20ºC for the immature stages and 23 - 30ºC to the adults; air moisture: 60 ± 10%; photophase: 14 h). The food ingested during the larval stage affected the viability of eggs, larvae and pupae, the length of larval and pupal stages and pupal weight. Two artificial diets were the most suitable: one composed by beans, casem, soybean flour, wheat germ and yeast, and other composed by beans and wheat germ and yeast only; both dieta may substitute the natural diet, i.e., wheat leaves for P. sequax rearing